Dampak Program Kawasan Rumah Pangan Lestari Terhadap Pendapatan Dan Pengeluaran Pangan Di Kabupaten Mempawah - Yohana S. Kusuma Dewi, Ade Kusuma Akbar, Abdul Hamid A. Yusra, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
Research objective is to analyses the impact of sustainable food house area (KRPL) of household income, comestible expenses, and consumption pattern in the village which receive KRPL aid. Research was conducted in Mempawah Regency West Kalimantan Province with survey methods by means of direct observation with sample and location which is pre-determined and selected deliberately. Data is collected by means of interview and using questioner. The result of this research show that there is differences in the income of household of KRPL aid receivers which is IDR 3.267.015 /month compared to non KRPL aid receivers which is IDR 2.851.282 /month. KRPL contribution to household income difference is IDR 99.125 /month, equal to 3,03% of total household income. While in terms of comestible expenses, research shows that percentage of total income spent for comestible is 59,44% for KRPL aid receivers and 59,48% non KRPL aid receivers, there is no significant difference between KRPL aid receivers and non KRPL aid receivers. These numbers indicate that comestible expenses, in low income household, tend to become major component of total expenses. Keywords: Comestible expenses; Household income; KRPL